Complete morphological re-description of mud-dwelling axiid Leonardsaxius amurensis (Kobjakova, 1937) with remarks on Axiidae (Crustacea: Decapoda: Axiidea) from the Russian coast of the Sea of Japan - Marin, Ivan (Zootaxa, 2015)
The first complete re-description of mud-dwelling axiid Leonardsaxius amurensis (Kobjakova, 1937) (Crustacea: Decapoda: Axiidea) is presented based on the holotype and freshly collected specimens from Vostok Bay, Russia coast of the Sea of Japan. The species is mostly morphologically similar to Leonardsaxius spinulicauda (Rathbun, 1902) known from Pacific coasts of North America from Vancouver to California but can be morphologically separated mainly by morphology of carapace and coloration of cornea of eyes. Remarks on distribution of Leonardsaxius amurensis (Kobjakova, 1937) and the second axiid species, Boasaxius princeps (Boas, 1880), known along Russian coastline of the Sea of Japan are given.